Factors Influencing Cost Performance Improvement on the Concept Of Green Retrofitting High-Rise Offices Using Structural Equationg Modelling-Part Least Square (SEM-PLS) - Wahyudi, Muhamad Aziz; Husin, Albert Eddy; Amalia, Nur (ASTONJADRO, 2023)
The increase in energy consumption in the operation of the building construction industry globally has increased by a percentage of 35%, so that this increase can lead to an increase in carbon emissions which was originally at a percentage of 28% to 38%. The concepts of Green Retrofitting, Dynamic Systems and Value Engineering can be researched based on the influence on improving the cost performance of Green Retrofitting in high-rise (existing) office buildings and connected with the Structural Equation Modelling-Partial Least Square (SEM-PLS) analysis model. PLS-SEM is very appropriate to be used in research aimed at developing theories. The results of this study show that in the application of the Green Retrofitting concept in high-rise office buildings using Dynamic Systems and Value Engineering has a significant effect on improving the cost performance of Green Retrofitting and get the most influential factors are Top Management Support, Energy Efficiency, Water Efficiency, Indoor Air Quality, Retrofitting Planning, Retrofitting Initial Costs, Bill Of Quantity,  Dynamic System Model Generation, Alternative Material Selection, and Material Cost Reduction